Study on Dynamic Load Monitoring of an Enhanced Stress Absorption Layer - Yang, Sanqiang; Li, Pengfei; Guo, Meng; Liao, Songyang; Wu, Haonan (Frontiers in Materials, 2020)
Asphalt pavement interlayer bonding and mechanical response have been hot topics in pavement research. In this paper, laying sensors on two kinds of stress absorption layers, the dynamic response laws of the two stress absorption layers were analyzed under different loads, speeds and temperatures. The results show that the asphalt pavement is a viscoelastic body and the measured results are consistent with the theoretical solution of layered elasticity: both stress absorbing layers are compressed. Five kinds of dynamic and static overload tests under the same conditions, the strain difference between the two sections increased from 11.6% of static load to 25.2% of dynamic load (40km/h). It indicates that the reinforced effect of geogrid is more obvious under dynamic load; By establishing the relationship between vehicle speed and dynamic response, a vehicle speed and dynamic response model for the enhanced stress absorption layer of slow crack (ESALOSC) is proposed; Based on the test data measured at four temperatures, a model of the temperature and dynamic response in the ESALOSC is proposed. The research results have important theoretical significance for improving the crack resistance of roads. At the same time, it provides technical support for the development of long-life pavement in China.